The Effectiveness of Using Canva as an Interactive Hypermedia In Learning English (Conference on English Language Teaching, 2023)
The aims of this study is to find out the effectiveness of using Canva as Interactive Hypermedia In Learning English. This research was conducted at Senior High School 1 Tasikmalaya. The research was carried out to the tenth grader student of SMA N 1 Tasikmalaya. X1 as the sample by using purposive random sampling. The result of the study shows that the use of Canva effective and improve the student’s English ability. It can be seen from the increasing students’ mean score in Learning English and The result of the of Students’ Questionnaire. The students active when working in a group and motivated learn English by using Canva. They enjoyed the activities during the learning process.